2020
DOI: 10.24018/ejbmr.2020.5.6.645
|View full text |Cite
|
Sign up to set email alerts
|

Personal Selling, Sales Promotion, and Intention Revisit: The Mediating Role of Reputation

Abstract: — The role of reputation as a mediator is used to explain the causality between personal selling and sales promotion with revisit intention. This research is an explanatory research, which aims to collect data from various sources and to verify the responses of 149 visitors to Nipah Mall Makassar. In testing the hypothesis, the data were analyzed using WarpPLS 7.0 analysis, the results of the study showed evidence that partially personal selling and sales promotion had a positive but insignificant effect on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
1
6
0
1
Order By: Relevance
“…Figure 3 below presents the geographical contexts where empirical studies were conducted. We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 3 below presents the geographical contexts where empirical studies were conducted. We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these generic natures of personal variables, there are some context-specific variables that are also studied about in tourist future travel behavior. Previous studies found that customer brand engagement, personal selling, emotion regulation ability, motivation, customer brand engagement, tourist happiness, perceived value, actual self-congruity, ideal self-congruity, e-WOM quantity, epistemic value has a positive effect on tourist revisit intention towards the destination during COVID-19 (Afriani and Sugiarto, 2020;Cifci, 2021;Ramli et al, 2021;Hu and Xu, 2021;Kadir et al, 2020;Ladiwala et al, 2021;Pinem et al, 2021;Rather, 2021a, b;Yu et al, 2021). A recent study found that Push motivation and pull motivation have a significant positive effect by revisiting intention (Sukaatmadja et al, 2022).…”
Section: Theoretical Perspectivesmentioning
confidence: 98%
See 3 more Smart Citations